"Conscious compassion": A co-created poetic representation of social workers' experiences with compassion. (May 2023) - Clark, Shelby L; Jen, Sarah
Arts-based research methods have an important place in social work scholarship. Arts-based research methods, such as poetic inquiry, highlight lived experiences through creativity, emotion, and embodiment. This paper shares findings from a qualitative study that investigated social workers' experiences with compassion in their professional practice through poetic inquiry. Findings are disseminated in a found poem that was collaboratively co-created by the researcher and study participants. The found poem highlights how compassion is a central and guiding force within social work practice. Compassion and connection remain core dimensions of the social work discipline and social work education, scholarship, and practice may benefit from continued exploration of compassion and related constructs.